The effect of different levels of cleanness of the pre-coat surface on adhesion and corrosion performance of A36 steel with epoxy coating - Widodo, Teguh Dwi; Setyarini, Putu Hadi; Sugiarto, Sugiarto; Raharjo, Rudianto; Bintarto, Redi; Darmadi, Djarot Bangun; Sagita, Sagita (SINERGI, 2026)
Adhesion and corrosion protection are the main properties of epoxy coatings, especially when applied to materials exposed to harsh environments, such as chloride-containing water. However, the adhesion and corrosion protection of coatings are affected by surface preparation, especially the cleanliness of the substrate surface prior to coating application. Choosing the proper surface preparation can optimize the coating's capabilities. This research aims to evaluate the Effect of blasting process cleanliness on coating performance on the steel surface. The novel approach is to correlate NACE surface cleanliness standards with coating performance. In this study, A36 steel is used. The cleaning procedure uses an air-blasting process with an 8-bar nozzle pressure and at least 5 minutes of spraying time to meet the desired National Association of Corrosion Engineers (NACE) standard. The abrasive utilizing garnet with a mesh of 30-40. Meanwhile, coating is performed at room temperature using the airless spray method with a 90° angle, a distance of 25 cm from the substrate and the nozzle, and a nozzle speed of 300 mm/s. The gap in the coating process between the first and second layers is 24 hours. The results showed that surface preparation influenced the coating's pullout strength and corrosion performance. The pullout strength test demonstrated that NACE 2 provided the highest pullout strength. Likewise, corrosion rate testing showed that surface preparation affects the corrosion rate, with NACE 1 providing the lowest corrosion rate (the best corrosion protection).